SimAlba: A Spatial Microsimulation Approach to the Analysis of Health Inequalities - Campbell, Malcolm; Ballas, Dimitris (Frontiers in Public Health, 2016)
This paper presents applied geographical research based on a Spatial Microsimulation model, SimAlba aimed at estimating geographically sensitive health variables in Scotland. SimAlba has been developed in order to answer a variety of 'what-if' policy questions pertaining to health policy in Scotland. Using the SimAlba model, it is possible to simulate the distributions of previously unknown variables at the small area level such as; smoking, alcohol consumption, mental well-being and obesity. The SimAlba microdataset has been created by combining Scottish Health Survey (SHS) and Census data using a deterministic reweighting Spatial Microsimulation algorithm developed for this purpose. The paper presents SimAlba outputs for Scotland’s largest city, Glasgow and examines the spatial distribution of the simulated variables for small geographical areas in Glasgow as well as the effects on individuals of different policy scenario outcomes. In simulating previously unknown spatial data a wealth of new perspectives can be examined and explored. This paper explores a small set of those potential avenues of research and shows the power of spatial microsimulation modelling in an urban context.